Pulmonary Lesion in the Wounded with Severe Mine Explosion Injury - T. V. Smelaya (Общая реаниматология)
Mine explosion injury is referred to as a most severe battle surgical pathology. The severity of wounds is determined by the mutual lesion burden phenomenon and by the development of the systemic contusion-commotion syndrome. Abnormalities of vitally important organs and systems are detectable in the presence of the extreme degrees of shock, massive blood loss, and severe functional and metabolic disturbances. The manifestations of posthypoxic organopathy become the basic contents of traumatic disease. Respiratory failure is the leading syndrome in the pattern of organic impairments so respiratory support is one of the major components of intensive care.